Role of sulphate-based additives on the early age properties of Portland cement incorporating alumina-rich ladle furnace slag - Chee Lok Yong; Tee How Tan; Haider Hamad Ghayeb; Suhana Koting; Kim Hung Mo (Case Studies in Construction Materials)
Ladle furnace slag (LFS) is a by-product of the steelmaking industry, mainly comprises calcium aluminate in the form of C12A7, forming C3AH6 upon hydration, which offers lower strength lower strength than metastable products like CAH10 and C2AH8. Introducing sulphate into LFS enhances mechanical strength through the formation of ettringite. This paper proposes using different sulphate-based additive, namely calcium sulphate anhydrite (CS) and sodium sulphate (SS) to activate the early age properties of alumina-rich LFS blended cement, aiming to induce ettringite and calcium silicate hydrate (C-S-H). In the present work, CS and SS at 1 %, 3 %, and 5 % dosages are added to blended cement containing 25 % and 50 % LFS replacement to investigate the setting time, soundness and strength development. The inclusion of 5 % SS results in a reduction of 50–57 % in setting times for specimens with 25 % LFS compared to the control. Notably, 1 % CS exhibits superior mechanical strength in specimens containing 25 % LFS, with increment of 38 %, 85 %, and 49 % at 2d, 7d, and 28d, respectively. Despite the improved mechanical properties and shortened setting times with these additives, soundness remains within the standard expansion limits stipulated by EN 197–1. The hydration mechanism is examined through microstructural characterisation using FESEM, XRD, and TGA. Results indicate that CS addition promotes the formation of ettringite and C-S-H, while SS addition leads to gel-like structures with high Na precipitation, hindering the formation of ettringite. The findings show a strong correlation with the hydration products derived from the microstructural analysis.